The Effect Of Virginia Coconut Oil (VCO) On The Prevention Of Decubitus In Prolonged Bed Rest Patients - syafriati, ani (Sahabat Publikasi Kuu, 2024)
Decubitus is a condition where external pressure causes damage or injury to local tissue. Trauma and surgical wounds can cause damage to skin integrity, long-term pressure on the skin can also cause irritation and the formation of decubitus, People who experience nerve damage due to stroke, traumatic injury, diabetes mellitus, or coma are also more likely to experience decubitus. The purpose of this study was to determine the effect of administering virgin coconut oil (VCO) on the risk of decubitus. The research method used the Pre Experiment design method with a one group pre post test design. The population in this study were all patients in the Akasia Inpatient Room, Siti Fatimah Az-Zahra Hospital, South Sumatra Province. The total number of patients treated was 30 respondents. Sampling was carried out using the total sampling technique. The results of the study showed that there was an effect of administering virginia coconut oil on the risk of decubitus in patients with long-term bed rest, the significant value of the non-parametric statistical test (Wilcoxon) was 0.000 (p value 0.000 <0.05). Suggestions are expected as input and sources of information in providing counseling to patients who are bedridden for a long time to use pharmacological therapy in preventing decubitus, and routinely use Virginia Coconut Oil which has many benefits.